A missing link in understanding Party policy change? Conservative Party international volunteering projects and UK development policy (2007–2017). (August 2019) - Beswick, Danielle; Hjort, Mattias
This article analyses the rationale for and impacts of Conservative Party overseas volunteering projects from 2007 to 2017. Using interview data and participant observation, we uncover aims of project founders and explore impacts of volunteering on Party members and policy. We make three substantial contributions. The first focuses on the survival of Conservative Party modernisation strategies launched under David Cameron. Support for development, particularly Party pledges to spend 0.7% of UK gross national income on aid, are poorly explained by existing research. We argue that a focus on volunteering helps explain the survival of this commitment. Second, we argue that volunteering experience may support sustained Party policy change by enhancing 'issue ownership'. Our final contribution is providing the first analysis of political parties as development-volunteer sending communities. Through new data and distinctive contributions, we demonstrate that understanding Party-supported volunteering promotes improved explanations of Party modernisation persistence and policy change.